Een nieuwe bijdrage aan de receptiegeschiedenis van het Tweede Vaticaans Concilie - van den Bos, Maarten (Religie & Samenleving, 2014)
Historians have hinted at the importance of the reception of the Second Vatican Council in the day to day practice of ordinary churchgoers, but an in depth analysis of this aspect of the council’s reception is not yet available. In this article new possibilities enabled by the composition of large repositories of digitized newspapers are explored. Using innovative tools for mining public discourses in larger textual repositories, two central questions are brought to the fore: what were central themes in the day to day newspaper reports on the council and how can the influence be measured of the conciliar debates and documents on different important topics debated in postwar Dutch newspapers. Central conclusion of the article is that the use of digitized newspapers and innovative tools is promising, as long as their disadvantages are taken into account.